ANALISIS FINANCIAL DISTRESS MENGGUNAKAN METODE ALTMAN, SPRINGATE, ZMIJEWSKI DAN INTERNAL GROWTH RATE PADA PERUSAHAAN TELEKOMUNIKASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Poppy Camenia Jamil; Iffa Vadilla As’ad (UIR Press, 2022)
Telecommunications service providers are competing to get clients to utilize their services due to the rapid advancement of technology. If, on the other hand, the company is unable to compete, it will go bankrupt. The Altman Z-score, Springate, Zmijewski, and Internal Growth Rate models were used to determine the probability of bankruptcy in telecommunications businesses listed on the BEI. This research uses descriptive analysis method with quantitative approach. The population in this study were telecommunication companies listed on the Indonesia Stock Exchange by using purposive sampling method to obtain 5 telecommunication companies, namely PT Bakrie Telcom Tbk, PT XL Axiata Tbk, PT Smartfren Tbk, PT Indosat Tbk, and PT Telkomunikasi Indonesia Tbk. Data were analyzed using Altman, Springate, Zmijewski, and Internal Growth Rate methods. The results showed that of the five most consistently good companies overall, PT Telekomunikasi Indonesia, three could still be said to survive, and one company (PT Bakrie Telcom) was declared to be in a state of crisis or financial difficulty.